Study on The Effect of pH Towards Copper (II) Bromide Reaction in Surfactant Determination - Mohamad Adam, Hanis Sufi; Hashim, Nor Haslina (Progress in Engineering Application and Technology, 2024)
Surfactants in cleaning products harm water quality. Anionic surfactants (AS) are particularly harmful. The current method to detect AS is difficult and requires toxic solvents. A new spectrophotometric method is needed to quickly and easily detect AS in water. This study employed copper (II) bromide metal salts because to their colour, water solubility, and stability. Utilizing the influence of pH on the reaction between certain Copper (II) Bromide (CuBr2) metal salts, Sodium Dodecyl Sulphate (SDS), and Triethylamine (TEA), the absorbance value at 650 nm wavelength is determined, and a calibration curve is created. The linear equation y = 0.2528x + 0.0246, is used to calculate SDS concentration from absorbance at various pH levels, with a very accurate fit indicated by an R² of 0.9974. This research study explores the optimization of surfactant detection utilizing CuBr2 as an indicator by systematically adjusting the sample's pH. The study aims to determine the ideal pH range that guarantees, building on the effective usage of CuBr2 in surfactant testing. The study involves a thorough examination of the indicator's performance under varied pH conditions, aiming to enhance the reliability of results and improve the ability to detect surfactants at various concentrations. From this study, the result shows that the shifted pH change the concentration of surfactant in the water sample. There is a small variation in the concentration measurement at pH 4 between the initial concentration of 0.1 and 30%, which is 0.1 to 0.7. This indicates that the surfactant's behavior is sensitive to pH changes. The change is relatively slight. It suggests that the surfactant's efficacy or behavior might be altered in this pH environment, possibly affecting its cleaning ability, toxicity, or interaction with other chemicals or biological entities in the water.